Seasonal evolution of Titan's stratosphere during the Cassini mission - Teanby, N; Sylvestre, M; Sharkey, J; Nixon, C; Vinatier, S; Irwin, P (Wiley, 2019)
Titan's stratosphere exhibits significant seasonal changes, including breakup and formation of polar vortices. Here we present the first analysis of midinfrared mapping observations from Cassini's Composite InfraRed Spectrometer to cover the entire mission (Lₛ=293–93°, 2004–2017)—midnorthern winter to northern summer solstice. The north polar winter vortex persisted well after equinox, starting breakup around Lₛ∼60° and fully dissipating by Lₛ∼90°. Absence of enriched polar air spreading to lower latitudes suggests large‐scale circulation changes and photochemistry control chemical evolution during vortex breakup. South polar vortex formation commenced soon after equinox and by Lₛ∼60° was more enriched in trace gases than the northern middle‐winter vortex and had temperatures ∼20 K colder. This suggests that early‐winter and middle‐winter vortices are dominated by different processes—radiative cooling and subsidence‐induced adiabatic heating respectively. By the end of the mission (Lₛ=93°) south polar conditions were approaching those observed in the north at Lₛ=293°, implying seasonal symmetry in Titan's vortices.